2004
DOI: 10.1016/j.urology.2004.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behavior and sexual dysfunctions after age 40: The global study of sexual attitudes and behaviors

Abstract: The results of our study indicate that sexual desire and activity are widespread among middle-aged and elderly men and women worldwide and persist into old age. The prevalence of sexual dysfunctions was quite high and tended to increase with age, especially in men. Although major between-country differences were noted, this global study revealed some clear and consistent patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
288
2
26

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 527 publications
(337 citation statements)
references
References 25 publications
21
288
2
26
Order By: Relevance
“…The GSSAB study reported the global prevalence of PE (based on subject self-report) to be approximately 30% across all age groups. 15,16 Similar results by age groups were also reported by the Brazilian Sexual Life Study: PE was reported in 25.8% of 3332 Brazilian men. 17 JaspersenGastelum et al 18 reported a high prevalence rate in older age groups.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The GSSAB study reported the global prevalence of PE (based on subject self-report) to be approximately 30% across all age groups. 15,16 Similar results by age groups were also reported by the Brazilian Sexual Life Study: PE was reported in 25.8% of 3332 Brazilian men. 17 JaspersenGastelum et al 18 reported a high prevalence rate in older age groups.…”
Section: Discussionsupporting
confidence: 82%
“…Data from the Global Study of Sexual Attitudes and Behaviors (GSSAB), an international survey investigating the attitudes, behaviors, beliefs and sexual satisfaction of 27 500 men and women aged 40 --80 years, reported that the global prevalence of PE (based on subject self-report) is approximately 30% across all age groups. 15,16 Many studies have found age to be a predisposing factor for EjD. EjD increases with advancing age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rates were 13% to 14% in Northern Europe, Southern Europe, Central and South America, and the Middle East. In the non-European West, the rate was higher at 21% but, as reported in the studies by Nicolosi et al, 20,42 the highest prevalence rates for ED were in two regions in Asia (27% in East Asia and 28% in Southeast Asia).…”
Section: Erectile Dysfunctionmentioning
confidence: 51%
“…The overall prevalence rate was 16% and the individual rates from the seven countries except the United States were below this rate, with the overall prevalence rate of ED in the United States being 22%. 41 In a second study from Nicolosi et al, 20 regional prevalence rates for 40 to 80 years of age from around the world were reported. Rates were stratified for age for all the countries and were low before 60 years of age, 15.2% for the seventh decade of life, and 22% for older than 70 years.…”
Section: Erectile Dysfunctionmentioning
confidence: 97%